PENGARUH MANAJEMEN PENGETAHUAN DAN PEMBELAJARAN ORGANISASIONAL TERHADAP PENGEMBANGAN KARIR DAN KINERJA KARYAWAN PT. PEGADAIAN (PERSERO) KANWIL II PEKANBARU - Legina, Muthia; Machasin, Machasin (Jurnal Tepak Manajemen Bisnis, 2017)
This research was conducted at PT Pegadaian (Persero) Kanwil II inPekanbaru. This research aimed to observe the effect of knowledge management andorganizational learning on career development and employeesâ performance.This researchused 138 respondents as sample and used purposive sampling as sampling method. Pathanalysis used to determine the effect of career development as mediating variable in therelationship between knowledge management and organizational learning to employeesperformance.The result showed that knowledge management and organizational learninghad significant effect on career development, then knowledge management and careerdevelopment were also having significant effect on employeesâ performance. Besidethat, career development mediated the relationship between knowledge management andorganizational learning on employeesâ performance.